Islamic education in Indonesia and Malaysia: shaping minds, saving souls - Azmil Tayeb (Routledge contemporary Southeast Asia series, 2018)
Functionalization of Islamic education in Indonesia and Malaysia -- Overview of state functionalization of national education in Indonesia and Malaysia (late 1800s to present time) -- The two verandahs of Mecca : Islamic education in Aceh and Kelantan -- Image of tolerance : Islamic education in Nusa Tenggara Timur and Sarawak -- Fusing the sacred and the profane : integrated Islamic education in Indonesia and Malaysia